A Rare Case of Type A Niemann-Pick Disease and its Treatment Approaches - Vignesh, Venugopal; Kalaivani, Sivakumar; Lokeshvaran, Deivendran; Aswin, John; Abinish, Dyneese Geetha (Indian Journal of Pharmacy Practice)
Niemann-Pick disease is a rare genetic lysosomal storage disorder characterised by disrupted lipid metabolism, leading to harmful lipid accumulation in organs such as the liver, spleen and brain. It is classified into several types, with Type A being the most severe and often fatal in early childhood, while Type B presents with milder symptoms. The diagnosis is based on clinical presentation and is confirmed through genetic testing. Current therapeutic approaches, including enzyme replacement therapy, show potential benefits by reducing lipid storage and improving clinical outcomes. This case report presents a 1-year-old male with global developmental delay and hepatosplenomegaly presented with a sudden seizure, along with a history of fever, cold and cough. Examination revealed febrile status, pallor, abnormal facies and a systolic murmur. Laboratory findings showed anaemia and mild hyperbilirubinemia and imaging revealed hypomyelination. Genetic testing confirmed Niemann-Pick disease Type A. The patient was referred to a specialised centre for enzyme replacement therapy and multidisciplinary care. This case underscores the potential of enzyme replacement therapy in improving outcomes for Niemann-Pick Disease, while highlighting the challenges of high costs, limited tissue penetration and the blood-brain barrier. Early diagnosis and specialised care remain critical in managing this condition and future research should focus on adjunctive therapies to enhance treatment efficacy.
Keywords: Case report; Enzyme replacement therapy; Lysosomal disorder; Niemann-Pick disease; Niemann-Pick Type A